Peningkatan Kinerja Guru dalam Mengajar melalui Penerapan Supervisi Klinis Berbasis Focus Group Discussion di SD Negeri 2 Trayu - Sumarmi Sumarmi (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The aims of this study are to 1) describe the steps for implementing clinical supervision to improve teacher performance in teaching, and 2) describe improving teacher performance in teaching. The results showed that the implementation of clinical supervision based on Focus Group Discussion (FGD) had gone well and was in accordance with the proper procedures. The steps for implementing clinical supervision based on Focus Group Discussion (FGD) carried out by researchers as school principals go through 6 stages, namely 1) Determining moderators and incentives for participants, 2) Preparing teams and implementation plans, 3) Implementation of Focus Group Discussions (FGD) , 4) Recording and summarizing substance, 5) Viewing and analyzing data, and 6) Processing data and making decisions. The implementation of the school principal's clinical supervision on teacher performance in teaching at SD Negeri 2 Trayu gave very satisfactory results. This can be seen from the realization of teacher professional competence in schools which includes teacher skills in preparing lesson plans, managing and implementing learning and conducting learning evaluations which are indicators of professional teachers. Based on the results of the study it can be concluded that the implementation of clinical supervision based on Focus Group Discussion (FGD) has been proven to significantly improve teacher performance in teaching. In the initial conditions the average value of teacher performance in teaching only reached 69.62 with category C (low), in cycle I it increased to 78.77 with category B (moderate) and at the end of cycle II it became 89.55 with category A ( Tall). Thus the teacher performance indicators in teaching through the application of clinical supervision based on Focus Group Discussion (FGD) at SD Negeri 2 Trayu semester 2 of the 2022/2023 school year of ≥ 75.00% of teachers obtained the high teacher performance category with a score range of 86 – 100 has been achieved ..